Print Collector's Quarterly - Keppel, Frederick; Carrington, Fitzroy (Londen : Frederick Keppel & Co., 1911)
The Print Collector's Quarterly (initially hyphenated as The Print-Collector's Quarterly), was a quarterly periodical that was begun in 1911 and continued under various publishers until 1950. The original founders were art dealer Frederick Keppel and art historian, Fitzroy Carrington.(Wikipedia)
Https://en.wikipedia.org/wiki/The_Print_Collector%27s_Quarterly
Online: https://commons.wikimedia.org/wiki/Category:The_Print_Collector%27s_Quarterly
Online: https://archive.org/search.php?query=the%20print%20collector%27s%20quarterly
Engels
Tijdschriften